Auditory attention in childhood and adolescence: An event-related potential study of spatial selective attention to one of two simultaneous stories. (June 2015) - Karns, Christina M.; Isbell, Elif; Giuliano, Ryan J.; Neville, Helen J.
Highlights: We measured auditory ERPs in children ages 3–16 years using a naturalistic dichotic listening task. ERP morphology differed for nonlinguistic versus linguistic probes in attended and unattended stories. Maturational changes were different for nonlinguistic versus linguistic probes. Attention modulated the amplitude of early-latency ERPs and invoked later sustained processes. Development of attentional processes was not uniform for different probe types. Abstract: Auditory selective attention is a critical skill for goal-directed behavior, especially where noisy distractions may impede focusing attention. To better understand the developmental trajectory of auditory spatial selective attention in an acoustically complex environment, in the current study we measured auditory event-related potentials (ERPs) across five age groups: 3–5 years; 10 years; 13 years; 16 years; and young adults. Using a naturalistic dichotic listening paradigm, we characterized the ERP morphology for nonlinguistic and linguistic auditory probes embedded in attended and unattended stories. We documented robust maturational changes in auditory evoked potentials that were specific to the types of probes. Furthermore, we found a remarkable interplay between age and attention-modulation of auditory evoked potentials in terms of morphology and latency from the early years of childhood through young adulthood. The results are consistent with the view that attention can operate across age groups by modulating the amplitude of maturing auditory early-latency evoked potentials or by invoking later endogenous attention processes. Development of these processes is not uniform for probes with different acoustic properties within our acoustically dense speech-based dichotic listening task. In light of the developmental differences we demonstrate, researchers conducting future attention studies of children and adolescents should be wary of combining analyses across diverse ages.